1989
DOI: 10.1042/bj2620965
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-induced accumulation of pyrophosphate in mitochondria during acetate metabolism

Abstract: The mechanism of pyrophosphate (PPi) accumulation in rat liver during acetate metabolism was investigated. Perfusion of the liver with acetate in the presence of noradrenaline and glucagon induced marked accumulation of PPi (2 mumol/g of liver, 200 times that of control). In contrast, perfusion with glutamine, which generates PPi only in the cytosol, caused little accumulation of PPi, even in the presence of the two hormones. The site of PPi accumulation was shown to be the mitochondria by the finding that iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 36 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Unlike the situation in liver (Davidson and Halestrap, 1988;Yamada et al, 1988;Inoue et al, 1989), no significant increases in tissue [PPJ] are observed in response to any of the treatments.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Unlike the situation in liver (Davidson and Halestrap, 1988;Yamada et al, 1988;Inoue et al, 1989), no significant increases in tissue [PPJ] are observed in response to any of the treatments.…”
Section: Resultsmentioning
confidence: 73%
“…Treatment of the perfused liver (Yamada et al, 1988;Inoue et al, 1989) and isolated hepatocytes (Davidson and Halestrap, 1988) with hormones that raise intracellular [Ca2"], or exposure of isolated mitochondria to physiological concentrations of Ca2l (Davidson and Halestrap, 1987), leads to a substantial increase in mitochondrial-matrix [PPJ]. This occurs as the result of the inhibition of mitochondrial pyrophosphatase by Ca2+, an effect mediated by the formation of CaPPi, which is a very potent competitive inhibitor of the enzyme with respect to MgPPi (Davidson and Halestrap, 1989;Baykov et al, 1989a).…”
Section: Introductionmentioning
confidence: 99%
“…Ringer's acetate solutions may create metabolic alterations. Inoue and colleagues 59 explored acetate metabolism using a liver rat model and showed that Ringer's acetate was associated with pyrophosphate accumulation inside the mitochondria, a phenomenon that could potentially lead to mitochondrial dysfunction. In the past, Ringer's acetate was used routinely in haemodialysis units, but these limitations and studies suggesting a vasodilatory and cardio-depressant effect of acetate 60 -64 have restricted its use.…”
Section: Discussionmentioning
confidence: 99%